The Philosophy of Happiness in Selected Works of N. M. Karamzin: The Search for True Bliss. (2nd January 2018) - Abramzon, Tatiana
ABSTRACT: This paper deals with the philosophy of happiness as found in N.M. Karamzin's poetry, publicistic texts, and Letters of a Russian Traveller, and it also examines certain key stages in the formation of Karamzin's concept of happiness and its features as found in certain of his works. When Karamzin broke off relations with the Masons and returned from a journey abroad, in Letters of a Russian Traveller (1791–1792) he proposes to readers various points of view about happiness which are not reduced to a rigid system: the author creates a narration which is fundamentally open for the reader's comprehension and where deep philosophical views are balanced with the author's irony or everyday naive tales about happiness. In his philosophical and publicistic essay "On the Happiest Time in Life" (1803). Karamzin enters into an open dispute with the ancient world and its philosophers over the issue of happiness proving that it is not attainable on earth and catching these philosophers out in a deception. Karamzin's philosophy of happiness is based on a synthesis of the ancient world and European enlighteners' concepts of happiness and the key core of this takes ethics as its starting point; however, true happiness and bliss are again relegated to heaven.